Proteasome and heat shock protein 70 (HSP70) inhibitors as therapeutic alternative in multiple myeloma - Pereira Eugenio, Angela Isabel [UNIFESP] (2020)
Conselho Nacional de Desenvolvimento Cientifico e Tecnologico (CNPq), Brazil